Performances mito-narrativas no ensino de história - Pacheco, Daniela Cristina (2016)
The study investigates the inclusion of mythical storytelling activities in classrooms connected to history teaching. It examines the didactic innovation as teaching-learning and performance methodology in the classroom. The myth-narrative performances are approached as a vehicle to facilitate learning, making changes in students' thinking about the different concepts of history and mythology. Myth is an important document for the understanding of a society, a period, an ethnic group and the mythical-literary narratives contribute to greater questioning of past-present relationship through impressions, aspirations and experiences of the individuals who coined them and factors that allow us to explain / understand the past. The relevance of the research is the possibility of contributing to studies of history teaching because it allows us to rethink the practice of the historian as researcher / lecturer in an inseparable perspective by effectively contributing to a differentiated, innovative and interdisciplinary approach.